The Influence of CEO's Overseas Background on Firms' Green Technology Innovation Based on the Moderating Effect of the Nature of Firms' Property Rights - Zhang, Hanghang (Transactions on Economics, Business and Management Research, 2024)
Based on China's current emphasis on green development and the bottleneck of green innovation faced by enterprises in practice, this paper focuses on analyzing the role of executives' overseas experience in corporate green innovation. Utilizing data from A-share listed companies in China from 2008 to 2022, this study finds that CEOs with overseas experience significantly promote corporate green technology innovation. The study further reveals the intrinsic mechanisms by which CEOs with overseas experience promote firms' green technological innovation, including the positive impact of their internationalized vision, environmental protection concepts and long-term planning on firms' innovation decisions. Meanwhile, the study also takes into account the heterogeneity of firms, and finds that the overseas experience of CEOs in private firms has a more significant effect on green technological innovation than that of state-owned firms. Through empirical research, this paper clarifies the influence mechanism and boundary conditions of CEOs with overseas experience on corporate green technology innovation, which provides useful insights for corporate management practice and policy making.